Pengaruh Profitabilitas, Pertumbuhan Penjualan, Capital Intensity, dan Ukuran Perusahaan terhadap Tax Avoidance - Arumtyas Safitri; Ickhsanto Wahyudi (CV. Multi Kreasi Media, 2022)
This study aims to determine the effect of Profitability, Sales Growth, Capital Intensity, and Company Size against Tax Avoidance on retail companies listed on the Indonesia Stock Exchange (IDX) during the 2018-2021 period, both partially and simultaneously. In this study, the independent variables used are Profitability proxied by the Return on Equity (ROE), Sales Growth, Capital Intensity, and Company Sizewith Ln (Total Assets) and the dependent variable Tax Avoidance. The population in this study are retail companies listed on the Indonesia Stock Exchange (IDX) for the 2018-2021 period. The research samples were 9 retail companies with a research period of 4 years to produce 36 samples obtained by purposive sampling technique. The data analysis method used is multiple regression analysis with SPSS. The results showed that the variables of Profitability, Sales Growth, Capital Intensity, and Company Size influence on each other simultaneously. Partially, Profitability variables have effect on Tax Avoidance, partially Sales Growth, Capital Intensity, and Company size no effect on Tax Avoidance.